The Influence of China's Belt and Road Initiative on Trade Dynamics in Central Asia - Iskakova, Danara (2025)
This study aims to assess the impact of the Belt and Road Initiative on trade dynamics in Central Asia. Launched in 2013, the BRI is a large-scale global infrastructure and investment project that will improve connectivity and economic co-operation in the world. Central Asia plays a crucial role in this initiative due to its geographical location. The study focuses on five Central Asian states - Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan - and assesses how participation in the BRI will affect their trade, infrastructure and economic growth. The work applies quantitative analyses, including correlation and regression models, as well as the evaluation of data taken from official international databases. In addition, qualitative analyses of academic literature, policy reports and articles will be conducted. Apart from the benefits, the BRI also faces challenges and criticisms regarding potential debt dependency, geopolitical tensions and environmental sustainability, which will also be addressed in this thesis. Finally, recommendations will be made to enhance positive and mitigate negative effects.